Turbulence statistics and distribution of turbulent eddies for jet flow and rigid surface interaction (Archives of Mechanics - Test, 2018)
The behavior of turbulent eddies within the self-similar region of a rigid surface interacting round jet is experimentally investigated. Results show that the turbulent jet flow structure is significantly affected due to the rigid surface interaction; particularly within the lower portion of the jet shear layer. It is observed that the jet and rigid surface interactions rather enhance the scale of axial velocity fluctuations within the intermediate region of the jet. An additional mixing layer is observed in the lower shear layer region close to the rigid surface due to the production of eddies from the rigid surface. The depth of penetration of the fluctuating eddies decreases significantly at the mixing layer region and this mixing layer acts like a shield which restricts the downward propagation of fluctuating eddies from the plane of symmetry of the jet. The results suggest that the region below the mixing layer can be treated as the shear less mixing region. The interesting consequence of this is that the rate of production of vorticity is enhanced below the mixing layer close to the rigid surface. Also, the enstrophy destruction is favored over enstrophy production at the upper portion of the mixing layer, and exactly the opposite phenomenon is observed in the lower portion of the mixing layer.